Hadroh in the Mosque from the Perspective of Imam Ibn Hajar al-Haitami and Imam Jalaluddin al-Suyuthi - Lafifah Ulfah Dalimunthe; Aripin Marpaung (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study aims to analyze the differences in opinion between Imam Ibn Hajar al-Haitami and Imam Jalaluddin as-Suyuthi regarding the law of performing hadroh in mosques. This study uses a normative sociological research method with a comparative approach. The types of research used are field research and library research. Primary data was obtained through interviews with the administrators of the Mosque Trust Board, hadroh members, and the community around the mosque, while secondary data was obtained from fiqh books, the works of Imam Ibnu Hajar al-Haitami and Jalaluddin as-Suyuthi, scientific journals, and other supporting literature. The results of the research show that Imam Ibnu Hajar al-Haitami allows the use of hadroh in mosques as long as it aims to spread Islam, does not contain elements of immorality, and maintains mosque etiquette. This opinion is based on the hadith regarding the use of duff in wedding ceremonies in mosques as well as the qiyas approach to other religious activities. Meanwhile, Imam Jalaluddin as-Suyuthi forbade the playing of hadroh in mosques because he considered it to diminish the honor and sanctity of the mosque as a place of worship. The differences in opinion between the two scholars were influenced by differences in the method of istinbat (legal determination), understanding of the function of mosques, use of evidence, and perspectives on art and entertainment in Islam. The practice of hadroh at the Al-Ihsan Tangguk Bongkar IX Mosque is generally carried out during religious activities such as birthdays, isra' mi'raj, and prayer meetings, so that it functions more as a medium for preaching and spreading Islam. After conducting Munaqasyah al-adillah, this research tends to clarify the opinion of Imam Ibnu Hajar al-Haitami as an opinion that is more relevant to the practice of hadroh in mosques, while still paying attention to the boundaries of the Shari'a, mosque etiquette and the solemnity of the congregation.